2017
DOI: 10.1016/j.ancard.2017.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carotid baroreceptor stimulation on retinal arteriole remodeling evaluated with adaptive optics camera in resistant hypertensive patients

Abstract: Background and Aim. Baroreceptor activation therapy (BAT) leads to a decrease in blood pressure (BP) in patients affected by resistant hypertension (RH) by reducing sympathetic outflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this review nine of the included articles were longitudinal studies. For example, Gallo and coworkers 19 found a significant difference in WLR before and after standard anti-hypertensive therapy with AO FIO, showing that subtle changes can be detected in a longitudinal study. Findings like this have a high relevance as they show that AO FIO is sensitive to small changes in retinal vascular biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…In this review nine of the included articles were longitudinal studies. For example, Gallo and coworkers 19 found a significant difference in WLR before and after standard anti-hypertensive therapy with AO FIO, showing that subtle changes can be detected in a longitudinal study. Findings like this have a high relevance as they show that AO FIO is sensitive to small changes in retinal vascular biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Several AO studies have observed that blood pressure management in hypertension can lead to the reversal of retinal microvascular changes. 73,78 For instance, a significant increase was observed in inner diameter and reduction in parietal thickness after antihypertensive treatment, 78 suggesting a reversal of eutrophic remodeling as a result of blood pressure changes. With regards to specific medication classes, however, AO imaging studies have presented discordant findings.…”
Section: Effect Of Antihypertensive Medications Using Adaptive Optics...mentioning
confidence: 99%